2023
DOI: 10.52851/cakrawala.v6i1.257
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Lingkungan Kerja, Profesionalisme dan Kepuasan Kerja Terhadap Komitmen Kerja Pada Unit Penyelenggara Bandar Udara (UPBU) Kelas I Mopah Merauke

Abstract: In theory, work commitment can be influenced by various factors, including the work environment, professionalism, and job satisfaction. Research on work commitment in the airport sector managed by the government is still very rare, therefore the purpose of this study is to determine the effect of the work environment, professionalism, and job satisfaction on employee work commitment at the Class I Mopah Merauke Airport Operations Unit (UPBU). with a population of 110. The sample determination method uses a sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…Previous studies have shown that workplace skills have a positive impact on employee work discipline at UPBU Merauke (Kasmawati et al, 2021;Kirwelakubun & Suprapti, 2023). Similarly, other studies show a relationship between work professionalism and employee work commitment at the airport (Gautama et al, 2023). Airport employees can have different characteristics, and this condition affects how they comply with the rules in the organization (Kirschenbaum et al, 2012).…”
Section: Current Conditions Of Quality Of Work Lifementioning
confidence: 82%
See 4 more Smart Citations
“…Previous studies have shown that workplace skills have a positive impact on employee work discipline at UPBU Merauke (Kasmawati et al, 2021;Kirwelakubun & Suprapti, 2023). Similarly, other studies show a relationship between work professionalism and employee work commitment at the airport (Gautama et al, 2023). Airport employees can have different characteristics, and this condition affects how they comply with the rules in the organization (Kirschenbaum et al, 2012).…”
Section: Current Conditions Of Quality Of Work Lifementioning
confidence: 82%
“…The second indicator is a healthy and safe work environment. This relates to work conditions that support the physical and mental health of employees (Gautama et al, 2023;Irdina et al, 2020;Tuchen et al, 2023). UPBU, besides functioning to manage and operate the airport in its area, providing comfort to passengers (Rositasari & Martanti, 2023), it is also a must to protect employees in terms of security and health (Tuchen et al, 2023).…”
Section: Current Conditions Of Quality Of Work Lifementioning
confidence: 99%
See 3 more Smart Citations